Forest cover changes in Indonesia’s terrestrial national parks between 2012 and 2017 - Asri Dwiyahreni; Habiburrachman A.H. Fuad; SUNARYO Sunaryo; TRI EDHI BUDHI Soesilo; Chris Margules; Jatna Supriatna (Society for Indonesian Biodiversity, 2021)
Tropical rainforests are among the most important ecosystems on earth. After Brazil, Indonesia has the second largest tropical forest area in the world. Since the 1970s, Indonesia’s forests have decreased from covering 87% to 50% of its land area. With the ever increasing pressures from economic and human development it appears likely that much of the biodiversity and ecosystem services provided by forest in Indonesia will only remain in conservation areas.  National parks currently cover around 60% or 16 Mha of the total area of protected areas in Indonesia. Between 2012 and 2017, 42 terrestrial national parks in Indonesia lost 1.07% of their total forest cover. However, primary forest cover increased by 0.07%. National parks in the Jawa Bali bioregion, through their natural mountainous conditions and ecosystem services to the surrounding areas, as well as better management inputs, have contributed to the increase of primary forest covers and keeping total forest loss relatively low in Indonesia’s national parks.